2011
DOI: 10.15835/nbha3915848
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Physicochemical Characterization of Winter Squash (Cucurbita moschata D.)

Abstract: Winter squash cv 'Cehualca' (Cucurbita moschata Duchense) is a seasonal crop that has been used as food and animal feed. The objective of the present study was to characterize physical, chemical and physicochemical properties of the winter squash cv 'Cehualca' . Morphological, chemical and physicochemical analyses were performed, including fiber, carotenoids, phenolic and mineral contents in the winter squash. The morphological analysis showed that the squash 'Cehualca' did not have a homogeneous morphology. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
33
4
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 17 publications
8
33
4
1
Order By: Relevance
“…While they reported it contains 0.10mg/100g for zinc and 0.16 mg/100g for iron. As for squash, the results are in range with results obtained by Jacobo-Valenzuela et al [31] they reported fat 0.04-0.14g/100g; ash 0.70-1.90 g/100g;. Minerals averaged around 0.31 mg/100g for iron and 0.24mg/100g for zinc.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While they reported it contains 0.10mg/100g for zinc and 0.16 mg/100g for iron. As for squash, the results are in range with results obtained by Jacobo-Valenzuela et al [31] they reported fat 0.04-0.14g/100g; ash 0.70-1.90 g/100g;. Minerals averaged around 0.31 mg/100g for iron and 0.24mg/100g for zinc.…”
Section: Discussionsupporting
confidence: 89%
“…Minerals averaged around 0.31 mg/100g for iron and 0.24mg/100g for zinc. While fiber was higher (1.48g/100g) than that reported by JacoboValenzuela et al [31] (0.85-1.24g/100g). The pH value of cantaloupe puree agrees with results of Syahidah et al [58], who reported the pH value to range between 6.46 and 6.48.…”
Section: Discussioncontrasting
confidence: 57%
“…Also, the same authors reported that the fruits had different sizes and color. Jacobo-Valenzuela et al (2008), AguilarGutiérrez et al (2009) andTamer et al (2010) reported values of color parameters L*, a* and b* in the pulp of Cehualca squash of 49.6-100.00, −3. 3-21.9 and −5.7-48.16;respectively.…”
Section: Morphologymentioning
confidence: 99%
“…Montes et al (2004) evaluated some physical characteristic of Cucurbita moschata and they reported that the fruits had different forms, colors, sizes, type of seed, seed color, etc. Jacobo-Valenzuela et al (2008) and Aguilar-Gutiérrez, Zazueta-Morales, and Camacho-Hernández (2009) evaluated morphological characteristics of winter squash cv. Cehualca (Table 1), found basic forms: type "Ovalada" (Oval), type "Bule" (form like bottle), type "Buchona" (maw), and type "Herradura" (Horseshoe).…”
Section: Morphologymentioning
confidence: 99%
See 1 more Smart Citation